Posterior circulation stroke diagnosis using HINTS in patients presenting with acute vestibular syndrome: A systematic review. (September 2019) - Krishnan, Kailash; Bassilious, Kerolos; Eriksen, Erik; Bath, Philip M; Sprigg, Nikola; Brækken, Sigrun Kierulf; Ihle-Hansen, Hege; Horn, Morten Andreas; Sandset, Else Charlotte
Abstract: Purpose: Acute vestibular syndrome – vertigo, nausea/vomiting, nystagmus and gait unsteadiness – is common, and differentiating posterior circulation stroke from a peripheral cause can be challenging. The National Institute of Health Stroke Scale (NIHSS) does not include acute vestibular syndrome, and early computed tomography scanning cannot rule out acute ischaemia. A positive Head Impulse–Nystagmus–Test of Skew (HINTS) test suggests posterior circulation stroke in acute vestibular syndrome when any of three signs are present: normal horizontal head impulse, gaze-direction nystagmus or eye skew deviation. This systematic review examined the accuracy of positive HINTS in identifying posterior circulation stroke in acute vestibular syndrome patients. Methods: We searched MEDLINE (1966 to 21 December 2017), EMBASE (1980 to December 2017), Web of Science and scanned bibliographies. Two authors independently screened relevant articles and extracted data. We included studies where HINTS was used to identify posterior circulation stroke with diagnosis confirmed using magnetic resonance imaging. Findings: Six studies (n = 644 patients) were identified. Acute stroke was confirmed in 200 (31.1%) patients. There was a 15-fold increased risk of posterior circulation stroke in patients with positive HINTS test compared to those with no abnormality (RR: 15.84, 95% CI: 5.25–47.79). For any stroke, the pooled sensitivity was 95.5% (95% CI: 92.6–98.4%) and specificity was 71.2% (95% CI: 67.0–75.4%). Discussion and Conclusion: The data suggest that the HINTS test as one element of clinical evaluation is useful to differentiate posterior circulation stroke from peripheral causes in acute vestibular syndrome. Further studies are needed to validate HINTS as a clinical prediction tool in emergency department settings and selection of patients for reperfusion treatment.